Linguagem e gozo: da intersubjetividade ao real do objeto a em Lacan - Santos, Rodrigo Oliveira dos (2023)
This work aims to understand how Lacan's notion of the real led him to abandon an understanding of the analytic experience as based on intersubjectivity. For that, it was necessary to situate the following steps: the real thought as the impossible of representation, an emptiness, an outside of the meaning irreducible to the signifier; the real as das Ding – both elaborated by Lacan (1959-1960/1988) in Seminar 7: The Ethics of Psychoanalysis (1959-1960/1988); and the real as object a – as elaborated in Seminar 10: Anxiety (1962-1963/2005). The first part of this work addresses how Lacan's orientation towards a field of language, based on the emphasis on the symbolic, led him to a definition of the unconscious ─ as part of the concrete, transindividual discourse, an insistence of the signifying chain ─ which was based on a understanding of the analytic experience as being of the order of intersubjectivity. This intersubjective relationship takes place in the formation of the subject, in the relationship with the Other, in a field of language. By way of a counterposition, in the second part, whose aim has its precedents still in Seminar 2: The Ego in Freud's Theory and in the Technique of Psychoanalysis, we argue that Lacan (1954-1955/1985) already anticipates the real as opaque, as the indeterminate navel of the dream, which is capable of making any imaginary and symbolic relationship with the Other that is guided by intersubjectivity and recognition fade away. In the third part, we explain that Lacan in Seminar 7: The Ethics of Psychoanalysis (1959-1960/1988) addressed the real as that which is not structured by language, as a hole in the symbolic, an outside of meaning in which the subject is excluded inside. Thus, beyond the subject in the intersubjectivity of his relationship with the Other mediated by the signifier, there is the real of the Thing, which is behind the subject and which works in the dimension of the cause. Finally, in the fourth part, we explain that, in Seminar 10: Anxiety (1962-1963/2005), Lacan invented the object a as the rest of the subjective operation in which the subject arises. The constitution of the subject in the place of the Other leaves a residue irreducible to the signifier and outside the signification, which is the object a. Anguish is a sign of the real, of object a, which is impossible to be represented and recognized by the subject. The object a corresponds to an absence of the signifier that is proper to the Thing, to a remainder, to the real that is beyond an intersubjective relationship, as it makes the Other, through a contraposition, barred, incomplete, lose its consistency.